Nutritional status of children hospitalized for parapneumonic effusion. - Koen Huysentruyt; Philippe Alliet; Marc Raes; Julie Willekens; Iris De Schutter; Elke De Wachter; Anne Malfroot; Thierry Devreker; Philippe Goyens; Yvan Vandenplas; Jean De Schepper (PLoS ONE)
Background & aims Among children hospitalized for pneumonia, those with parapneumonic effusion (PPE) are at particular risk for nutritional deterioration. This study aimed to 1) investigate the evolution of the nutritional status during hospitalization and at outpatient follow-up; 2) determine clinical risk factors for weight loss during hospitalization; 3) describe the nutritional interventions for these children. Methods Retrospective chart review (January '07 - September '12) of 56 children with pneumonia, complicated by PPE in two Belgian hospitals for data on body weight and height at admission (t0) and discharge (t1), and two weeks (t2) and one month (t3) after discharge. Length of hospitalization (LoS), length of stay in paediatric intensive care (LoSPICU) and maximal in-hospital weight loss (tmax) were calculated and nutritional interventions were recorded. Results The median (range) age was 3.5 (1.0-14.8) years. Weight or height was lacking in five (8.9%) children at t0 and in 28 (50%) at t1; 21.4% was weighed only once during hospitalization. At tmax, respectively 17/44 and 5/44 children lost ≥ 5% and ≥ 10% of their weight. Median (range) LoS and LoSPICU were 18.0 (10-41) and 4.0 (0-23) days. One-fourth received a nutritional intervention. Weight for height at admission (WFH(t0)) significantly predicted maximal weight loss (β (95% CI) = -0.34 (-2.0--0.1); p = 0.03). At t2 and t3, 13/32 and 5/22 of the children with available follow-up data did not reach WFH(t0), whilst in 4/35 and 5/26 body weight remained ≥ 5% under the weight(t0). Conclusions One-third of children with pneumonia complicated by PPE and monitored for weight and height, lost ≥ 5% of their body weight during hospitalization. One-fourth did not reach initial WFH one month after discharge. Those with a higher WFH at admission were at higher risk of weight loss. More attention for monitoring of weight loss and the nutritional policy during and after hospitalization is warranted.